VD_FINDINFO HC / 2011 / 83 vom 17. Februar 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, BASE DU REVENU, MODIFICATIONEN GÉNÉRAL, CONJOINT, OBLIGATION D'ENTRETIEN | 137 al. 2 CC, 176 al. 1 ch. 1 CC